Quantitative Assessment of the Development of Arctic Research - A. I. Terekhov (Ekonomika Nauki)
The article presents a brief bibliometric analysis and assessment of the development of research related to the Arctic. The world trends in the volume of scientific output are considered, significant countries prticipating in the research are identified, their contribution and the place of Russia are assessed, an international co-authorship network is built and studied. The rapid growth of world research in the Arctic in the last decade, driven by not only the Arctic countries, but also non-Arctic ones, and the growing international cooperation are shown. Russia, combining the traditionally strong position of Russian academic school in the study of the Arctic with the increasing activity of universities, significantly exceeded the average world growth rate and became the third in the world in terms of the volume of Arctic research. The main source of information for the analysis was the Web of Science Core Collection database, an additional source – Google Scholar